KAUSALITAS SERTA RESPONS PEREKONOMIAN, BELANJA PEMBANGUNAN TELEKOMUNIKASI PUBLIK DAN PENELITIAN PENGEMBANGAN DI INDONESIA - Zen, M Hafiz; Aimon, Hasdi (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract : This study aims to see causal relationship and response between the economy, public telecommunications development spending and research development expenditure in Indonesia. This study using a data starting from 1988-2019, using the Vector Autoregression (VAR) processing method. The results of this study indicate that: (1) There is no causality or reverse relationship between public telecommunications development spending and research development expenditure in Indonesia, (2) There is no causality relationship between research development expenditure and the economy in Indonesia, but there is a one-way relationship from the economy to research development expenditure in Indonesia, (3) There is a two-way causality relationship between public telecommunications development spending and economy in Indonesia, (4) There is an economic response due to public telecommunications development spending and research development expenditure shocks in Indonesia (5) There is a response to public telecommunications development spending due to economic and research development spending shocks in Indonesia (6) There is a response to research development spending due to economic and public telecommunications development spending shocks in Indonesia.Keyword : Economy, Public Telecommunications Development Spending and Research Development Expenditure